Utilizing residual waste particles from polyethylene terephthalate (PET) waste pellet production in cement mortar - Sudeep Koirala; Bisesh Hirachan; Santosh Gharti Chhetri; Tek Raj Gyawali (International Journal of Sustainable Engineering)
Polyethylene terephthalate (PET) bottle waste management is a global challenge, with PET pellet production generating 20-23% waste particles (PWP). These particles, when deposited in landfills, do not decompose and can disperse, posing health risks, while burning them releases hazardous gases. This study explores the use of PWP in masonry mortar by replacing sand at 0%, 5%, 10%, and 15% levels. Mortar mixtures with cement-sand ratios of 1:4 and 1:6, and a water-cement ratio of 0.50 were tested. The results showed that 5% PWP content improved mortar properties, including flow table value, water absorption, compressive strength, flexural strength, and splitting tensile strength, while reducing density and elastic modulus. Specifically, the 28-day compressive strength increased by 14.0% and 7.1% for the 1:4 and 1:6 mixes, respectively. The enhanced workability is attributed to the smooth, round shape, and zero water absorption of PWP particles, while the increase in mechanical strength is due to the pozzolanic properties of PWP. This solution addresses PWP waste management while improving mortar properties, contributing to sustainable construction practices, reducing sand usage, and promoting eco-friendly mortar and concrete production.